Optimalisasi Ruang Kelas Inklusif dengan Perbaikan Prasarana Kelas untuk Siswa Berkebutuhan Khusus di Sekolah Luar Biasa - Irfan Zhain Zhain; Prathita Muti’a Yuzaeva (Jurnal Abdi Karya Sipil, 2026)
Inclusive education is a national priority to achieve equal access to education for all citizens, including students with special needs. However, in many Special Education Schools, the availability of special classroom infrastructure that supports inclusive education is still limited or does not meet accessibility standards. This study aims to optimize inclusive spaces through improvements to special classroom infrastructure in SLB, with a focus on physical adjustments to the space, supporting facilities, and the creation of a learning environment that is friendly to students with special needs. The methods used included field observations, interviews with teachers, principals, and parents, and a needs analysis based on building accessibility standards. The results showed that after the improvement intervention, there was a significant increase in student, teacher, and parent satisfaction with the learning environment. Specifically, there was an increase in student confidence and the efficiency of the learning process.